2016
DOI: 10.1002/jcph.765
|View full text |Cite
|
Sign up to set email alerts
|

Precision Oncology Medicine: The Clinical Relevance of Patient‐Specific Biomarkers Used to Optimize Cancer Treatment

Abstract: Precision medicine in oncology is the result of an increasing awareness of patient specific clinical features coupled with the development of genomic-based diagnostics and targeted therapeutics. Companion diagnostics designed for specific drug-target pairs were the first to widely utilize clinically applicable tumor biomarkers (e.g. HER2, EGFR), directing treatment for patients whose tumors exhibit a mutation susceptible to a FDA approved targeted therapy (e.g. trastuzumab, erlotinib). Clinically relevant germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 129 publications
(223 reference statements)
0
64
0
Order By: Relevance
“…For example, targeted agents for the protein products of EGFR mutations have been extensively studied in non-small cell lung cancer with impressive results [78]. ERBB2 (HER2) positivity, frequently seen in invasive breast and gastric cancer, has been targeted effectively with a yield of improved outcomes [911, 15, 16]. However, other studies have suggested that some alterations cannot be targeted well, at least with single agents in the refractory metastatic setting.…”
Section: Introductionmentioning
confidence: 99%
“…For example, targeted agents for the protein products of EGFR mutations have been extensively studied in non-small cell lung cancer with impressive results [78]. ERBB2 (HER2) positivity, frequently seen in invasive breast and gastric cancer, has been targeted effectively with a yield of improved outcomes [911, 15, 16]. However, other studies have suggested that some alterations cannot be targeted well, at least with single agents in the refractory metastatic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical testing for genomic changes (biomarkers) can define diagnostic subtypes; predict tumour behaviour, prognosis, and drug response; and enable monitoring for early recurrence of disease2223…”
Section: Whole Genome Sequencing In Cancermentioning
confidence: 99%
“…To date most of these companion diagnostic assays have focused on relatively few analyte targets. However, the total number of mutations that have evidence for activity as a driver of tumor progression and that can be specifically targeted by a specific drug has grown to several thousand, shifting the precision medicine paradigm from 1-gene-1 drug to a multigene-many drugs model [6]. Multiplex testing strategies are needed to be developed to increase the number of tests that can be performed on limited biopsy samples.…”
Section: Molecularly Targeted Cancer Therapeuticsmentioning
confidence: 99%